Methodological quality of the injury surveillance system used in international athletics championships. Issue 12 (December 2016) - Edouard, Pascal; Branco, Pedro; Alonso, Juan Manuel; Junge, Astrid
Abstract: Objectives: Incidence and prevalence data obtained from injury surveillance studies could be biased by the response rate as well as by the completeness and quality of the reports. It therefore appears crucial to analyse the quality of the injury surveillance system itself and thereby validate the quality of the data. This study aimed to analyse the quality of and compliance with the injury surveillance system implemented during international athletics championships. Design: Prospective, epidemiological study. Methods: The national medical teams and the local organising committee physicians daily reported all injuries on a standardised injury report form during 14 international athletics championships from 2007 to 2015. The quality of the injury surveillance system was analysed following the guidelines laid down by the Centre for Disease Control and Prevention. Results: On average 41.7 ± 17.4% (mean ± standard deviation) of all registered countries participated in the injury surveillance project, accounting for a coverage of athletes of 79.5 ± 10.2% of all registered athletes. Their medical staff returned 89.2 ± 8.4% of the expected injury report forms (information is missing for one championship). The completeness of injury data provided by medical teams and local organising committee physicians averaged 95.8 ± 6.5%. National medical teams reported 60.6 ± 16.6% of all injuries, and local organising committee physicians 28.7 ± 15.0% whereas 10.6 ± 6.5% of injuries were reported by both. Conclusions: The injury surveillance system used during international athletics championships provided good national medical team participation, coverage of athletes, response rate, and completeness of reports. These parameters should be systematically reported for injury surveillance studies to show the quality of the study.